Primed mesenchymal stem cell-derived exosomes as a potential therapeutic strategy for inflammatory arthritis - 김미진 (The Graduate School, Ajou University, 2018)
Mesenchymal stem cells (MSCs) have emerged as a good source of cells for therapeutic applications. The therapeutic efficacy of MSCs has been demonstrated for a variety of target diseases, and MSCs have already obtained market approval in certain countries. The therapeutic efficacy of MSCs is attributed mainly to their paracrine secretion of cytokines and growth factors, which exert diverse cellular activities, such as immune modulation, anti-inflammatory effects, angiogenic effects, and neurogenesis. However, studies have shown that MSCs exert their paracrine effects by secreting not only trophic factors, but also exosomes. Exosomes are secreted vesicles of endocytic origin that are 55–100 nm in size and secreted by a variety of cells types, including MSCs. Exosomes mediate local or systemic cell-to-cell communication and alter cellular metabolism through the transfer of various proteins, mRNAs, and microRNAs (miRNAs). Recent studies have shown that MSC-derived exosomes mediate the therapeutic effects of MSCs, and suggest their potential as a cell-free therapy because of their lower immunogenicity, and ease of manipulation and storage, as compared to cell-based products. For example, MSC-derived exosomes have been reported to be therapeutically active for the treatment of osteoarthritis (OA); however, their ability to inhibit inflammation in OA has not yet been reported. Therefore, in this study we aimed develop exosomes as a therapeutic agent for inflammatory arthritis by improving their anti-inflammatory properties and increasing their production by priming MSCs. Chapter 1 describes our investigation of the anti-inflammatory effect and mechanism of exosomes, that were derived from MSCs primed with Interleukin-1 beta (IL-1β) (MSCs-IL-Exo), in SW982 human synovial cells treated with IL-1β and tumor necrosis factor alpha (TNF-α). We demonstrated that exosomes isolated from both unprimed and IL-1β-primed MSCs were round in shape and approximately 30-300 nm in size. Exosomes from both IL-1β-primed and unprimed MSCs also expressed CD9, CD63, and CD81 at similar levels, as shown by Western blot analysis. In the inflammatory model of SW982 cells induced by IL-1β and TNF-α, MSCs-IL-Exo showed higher inhibitory activity against IL-1β, IL-6, and MCP-1 than MSCs from unprimed MSCs (MSCs-Exo). Profiling of small RNAs demonstrated that the priming of IL-1β altered small RNA levels in exosomes secreted from MSCs. Moreover, among the anti-inflammatory miRNAs we examined, miRNA 147b (miR-147b) was present at higher levels in MSCs-IL-Exo than in MSC-Exo. Moreover, we found that transfecting inflammatory SW982 cells with miR-147b led to inhibition of IκBα degradation. These results suggest that MSCs-IL-Exo are more efficacious in inhibiting NFκB activation than MSCs-Exo, and that miR-147b shuttled by MSCs-IL-Exo may be involved. Chapter II describes our investigation of whether three-dimensional (3D) spheroid culture of MSCs improves the efficiency of exosome production and if so, the underlying mechanism. We adopted two models of 3D-spheroid culture using the hanging-drop (3D-HD) and poly 2 hydroxyethyl methacrylate (poly-HEMA) coating methods (3D-PH). The 3D-HD method formed a single large spheroid, while the 3D-PH method formed multiple smaller ones. MSCs cultured on both types of spheroids produced significantly more exosomes than those cultured in conventional two-dimensional (2D) monolayer cultures. We then investigated the effects of hypoxia, high cell density, and non-adherent cell morphology on exosome production. We observed that increased spheroid size was associated with greater exosome production, while the 3D-HD and 3D-PH methods produced the fewest cells. Increasing the cell density in 2D culture (2D-H) led to less efficient exosome production than conventional, lower cell density 2D culture. Finally, plating cells at a normal density on poly-HEMA coated spheroids (termed 3D-N-PH), led to the formation of small aggregates consisting of less than ten cells that produced more exosomes than 2D-cultured cells plated at the same density. Moreover, F-actin expression was markedly reduced in the 3D-N-PH culture. Together, these results suggest that 3D spheroid culture produces more exosomes than 2D culture and the non-adherent rounded cell morphology itself might be a causative factor. These results could provide useful information for developing an optimal process for the mass production of exosomes.
학위논문(박사)--아주대학교 일반대학원 :분자과학기술학과,2018. 8
Keywords: Mesenchymal stem cells (MSCs); Exosomes; Priming; Inflammatory arthritis; Three-dimensional (3D)